Clinical improvement following vitamin D3 supplementation in children with chronic tic disorders - Li HH (Dove Medical Press, 2019)
Hong-Hua Li,1 Zhi-Da Xu,1,2 Bing Wang,1 Jun-Yan Feng,1 Han-Yu Dong,1 Fei-Yong Jia1,31Department of Developmental and Behavioral Pediatrics, The First Hospital of Jilin University, Changchun, Jilin 130021, People’s Republic of China; 2Department of Psychiatry, University Medical Center Utrecht, Utrecht, The Netherlands; 3Neurological Research Center of the First Hospital of Jilin University, Changchun, People’s Republic of ChinaCorrespondence: Fei-Yong JiaDepartment of Developmental and Behavioral Pediatrics, The First Hospital of Jilin University, Changchun, Jilin 130021, People’s Republic of ChinaTel +86 04 318 878 3846Email erkekangfujia@163.comPurpose: Vitamin D deficiency has been found in children with chronic tic disorders (CTDs). Our previous data showed that serum 25-hydroxyvitamin D [25(OH)D] level in children with CTDs was lower than that of the healthy controls and lower serum 25(OH)D level was associated with increased severity of the tic disorder. Thus, we intend to further verify this phenomenon and examine the effect of vitamin D3 on CTDs.Patients and methods: In total, 120 children with CTDs and 140 normal controls were enrolled in this study, with 36/120 of those in the CTD group receiving vitamin D3 treatment for 3 months. The Yale Global Tic Severity Scale (YGTSS) and Clinical Global Impression of Severity of Illness (CGI-SI) were, respectively, used to evaluate the tic severity. High-performance liquid chromatography and tandem mass spectrometry were used to measure serum 25(OH)D level.Results: Those children with CTDs exhibited significantly lower 25(OH)D levels than did healthy controls, and these reduced 25(OH)D levels were linked to increasing severity of tic symptoms. After treatment with supplemental vitamin D3, serum 25(OH)D level and scores of YGTSS total, motor tics, phonic tics, total tic, impairment, and CGI-SI improved significantly in children with CTDs without any adverse reactions.Conclusion: Supplementation vitamin D3, given its low cost and excellent safety, may be an effective means of improving symptoms in certain children with CTDs.Keywords: vitamin D, chronic tic disorders, 25(OH)D, dopamine, child